2011
DOI: 10.1097/mbc.0b013e328343f7be
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative changes in procoagulant factors after major surgery

Abstract: Surgical patients are primarily at an increased risk of perioperative bleeding; however, after surgery, these patients develop hypercoagulability that favors thrombotic events. Currently, the time course of postoperative coagulation is not well characterized. Thus, the aim of the present study was to provide a detailed description of the changes in procoagulant factors in patients after major surgery and to evaluate coagulation tests based on their ability to detect hypercoagulability. Fifty-one consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 31 publications
5
49
0
4
Order By: Relevance
“…21 Because Lison et al excluded patients with cardiac surgery, these results and the presented data can only be compared to a limited extent. However, the tendency to higher platelet responsiveness appeared to be present in patients after cardiac surgery with CPB as well.…”
Section: Discussionmentioning
confidence: 93%
“…21 Because Lison et al excluded patients with cardiac surgery, these results and the presented data can only be compared to a limited extent. However, the tendency to higher platelet responsiveness appeared to be present in patients after cardiac surgery with CPB as well.…”
Section: Discussionmentioning
confidence: 93%
“…These clinically significant hemorheological and hemostasiological alterations include: Hyperreagibility of platelets with increased aggregation and adhesion tendency; changes in fibrinogen, albumin and globulin concentrations, which affect viscosity and erythrocyte aggregation and impairment of deformability; increase in clotting factors and disturbance of fibrinolysis (20)(21)(22). Patients undergoing surgical procedures have been subject to investigation, in which thrombin activation parameters, clotting factors, fibrinolysis and thrombelastographic changes were examined in order to determine whether hypercoagulation occurs (23)(24)(25)(26)(27). The present study revealed that no significant changes were observed for PT, APTT and TT; the mean level of antithrombin III was found to be significantly below preoperative values on POD1 and POD2, and the fibrinogen and D-dimer levels were increased continuously during the 7 days following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that hematological and nonhematological malignancies activate the blood coagulation system through the release of procoagulant factors, activation of the antifibrinolytic pathways, and the creation of an imbalance between pro-and antiinflammatory cytokines, which favor the production of peripheral clots in the majority of patients [16,17]. This procoagulant state may also continue into the postoperative period [18].…”
Section: Why Cancer Patients May Bleedmentioning
confidence: 99%
“…Patients with cancer are at risk for significant bleeding due to tumor-related factors such as proximity or invasion of major vascular structures or hypervascularization of the cancerous tissue itself [17,18]. Lastly, it is also well known that major tissue trauma as observed in extensive oncological surgery may alter the functional equilibrium between soluble plasma fractions, erythrocytes, leukocytes, platelets, and the fibrinolytic system.…”
Section: Why Cancer Patients May Bleedmentioning
confidence: 99%